PERAN SERTA MASYARAKAT DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN LAHAN GAMBUT DI JALAN SUKAMAJU KELURAHAN LANDASAN ULIN UTARA KOTA BANJARBARU - Jose Alphama; Fonny Rianawati; Arfa Agustina Rezekiah (Jurnal Sylva Scienteae, 2020)
This study aims to explore information on the causes of peatland fires that occur and assess the role of the community in efforts to prevent and control peatland fires on Sukamaju Road, North Landasan Ulin Village, Banjarbaru City. Based on the research results, the main causes of fires were 76% caused by unknown causes and spread to Jalan Sukamaju, 18% due to cigarette butts thrown carelessly, and 6% due to burning or land clearing carried out during the dry season. While for fire prevention efforts, residents plant fireproof plants with banana and papaya species, residents also make firebreaks in the form of trenches as deep as 1-2 meters between agricultural land to block fires while for fire prevention 80% of the population will report directly to the authorities if there was a fire because of the difficulty of extinguishing the fire on peatland while 20% extinguished the fire directly with makeshift equipment such as hoes or pouring water directly.Keywords: participation; community; fire, peat land